2021
DOI: 10.1186/s12887-021-02533-2
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioural and cognitive effects of prenatal exposure to organochlorine compounds in three year old children

Abstract: Background We report data of a Belgian observational prospective cohort study regarding cognitive and behavioural development until the age of 36 months in relation to internal exposure to organochlorine pollutants [sum of polychlorinated biphenyls (sum PCB), dioxin-like activity, PCB118, PCB170, hexachlorobenzene (HCB) and p,p’-dichlorodiphenyldichloroethylene (DDE)] measured in cord blood. Methods Participants were recruited as part of an Flemish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…All animal protocols were conducted in accordance with NIH and USDA guidelines and were approved by the Institutional Animal Care and Use Committee (IACUC) at The University of Texas at Austin. Sprague Dawley rats were obtained from Harlan Laboratories (Houston, TX, USA), switched to the low-phytoestrogen Harlan-Teklad 2019 Global Diet ad libitum, and housed in same-sex groups (2-3 per cage) under constant humidity and temperature (21)(22) • C) and a partially reversed 12:12 L:D cycle (lights on at 2400 h). Virgin females were impregnated in house.…”
Section: Experimental Design and Animal Husbandrymentioning
confidence: 99%
See 1 more Smart Citation
“…All animal protocols were conducted in accordance with NIH and USDA guidelines and were approved by the Institutional Animal Care and Use Committee (IACUC) at The University of Texas at Austin. Sprague Dawley rats were obtained from Harlan Laboratories (Houston, TX, USA), switched to the low-phytoestrogen Harlan-Teklad 2019 Global Diet ad libitum, and housed in same-sex groups (2-3 per cage) under constant humidity and temperature (21)(22) • C) and a partially reversed 12:12 L:D cycle (lights on at 2400 h). Virgin females were impregnated in house.…”
Section: Experimental Design and Animal Husbandrymentioning
confidence: 99%
“…Known as the Developmental Origins of Health and Disease or DOHaD [3], this phenomenon has been well studied for a variety of health outcomes in individuals who experienced direct exposure early in life (F1 generation). Regarding neuroendocrine functions and hormonedependent behaviors, the focus of this study, exposures to EDCs including bisphenol A (BPA), phthalates, and persistent organic pollutants such as polychlorinated biphenyls (PCBs) induce adverse phenotypic outcomes in animal studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17], and are associated with increased prevalence of neurobehavioral disorders in epidemiological studies in humans [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most heritable behavioural traits is intelligence or cognitive ability (often measured by general psychometric scale indexes or scores), with a heritability that rises from 20% in childhood to 70% in older adulthood [9]. However, previous research has revealed that a child's cognitive capacity is not just in uenced by genetics and that there are a number of other factors associated, such as socioeconomic status [10], the mother's gestational age [11], the mother's intelligence [12], family context [13], and, most importantly for this study, prenatal exposure to detrimental environmental factors such as cigarette smoke, organochlorine pollutants, maternal malnutrition, obesity, or stress, among others [14][15][16][17][18]. Thus, it is thought that placental function, and in particular placenta DNAm, could be a plausible mechanism contributing to this prenatal environmental in uence on cognitive functions later in life.…”
Section: Introductionmentioning
confidence: 99%
“…Animal models of the “developmental origins of health and disease” (DOHaD) hypothesis show cause-and-effect relationships between early life exposures to individual EDCs and abnormalities in cognitive, affective, and social behaviors later in life [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Epidemiological evidence in humans suggests that those with higher body burdens of EDCs may have a greater propensity for aberrations in these same behaviors [ 10 , 11 , 12 , 13 , 14 ]. Specific to anxiety-like disorders, these relationships have been shown, to date, for bisphenol A (BPA) [ 15 , 16 , 17 , 18 ], phthalates such as DEHP [ 19 , 20 ], and persistent organic pollutants such as polychlorinated biphenyls (PCBs) [ 21 , 22 ] in both rodent and human studies.…”
Section: Introductionmentioning
confidence: 99%